Characterization of clay intercalated cobalt-salen catalysts for the oxidation of p-cresol - Kshirsagar, V. S.; Garade, Ajit C.; Mane, R. B.; Patil, K. R.; Yamaguchi, A.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2009)
The intercalation of cobalt-salen complexes into the interlamelar spaces of montmorillonite clay was investigated by various characterization studies. The ``neat'' cobalt-salen complex showed a weight loss at 368 degrees C while the weight loss for the corresponding intercalated complex was observed at much higher temperature of 492 degrees C due to decomposition of the complex. The thermal stabilization observed was due to the host-guest interaction of clay and metal complex and thus confirmed the intercalation. The XANES spectrum of Co(salen)-mont sample revealed the change of symmetry from the tetrahedral in plane to the octahedral structure having an axial bonding of oxygen to the cobalt, indicating that cobalt atoms in Co(salen)-mont were coordinated axially with the lattice oxygen of montmorillonite. Both XANES and EXAFS results indicated that cobalt atoms in Co(salen)-mont form two additional Co-O bonds with a bond length of 0.199 nm by the intercalation while retaining the Co-salen structure. Co-salen intercalated into the montmorillonite clay showed the highest activity for the air oxidation of p-cresol, giving 88% selectivity to the oxidation products. Effects of NaOH concentration and various solvents on the conversion and selectivity patterns also have been studied. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cobalt-oxygen bond; Cobalt-salen; Extended X-ray absorption fine structure; Intercalation; Lattice oxygen; Montmorillonite; X-ray absorption near edge structure

Copper modified waste fly ash as a promising catalyst for glycerol hydrogenolysis - Rode, C. V.; Mane, R. B.; Potdar, A. S.; Patil, P. B.; Niphadkar, P. S.; Joshi, P. N. (Catalysis Today, 2012)
Several catalyst formulations using waste fly ash along with Cu were prepared and characterised by XRD, BET and TEM. These catalysts were also evaluated for the first time for hydrogenolysis of glycerol to 1,2 propanediol (1,2-PDO) in a batch reactor under 52 bar H-2 pressure in the temperature range of 473-513 K conditions. The fly ash pretreated by alkali using the fusion method and impregnated with Cu showed higher activity and stability for glycerol hydrogenolysis. Due to pretreatment with alkali at high temperature, transformation of alpha-quartz to the tridymite phase of SiO2 occurred. More importantly, use of alkali either during the pretreatment or the Cu loading step resulted in a high dispersion on the surface which was responsible for higher glycerol conversion and 1,2-PDO selectivity. The effects of temperature, Cu loading and solvent on glycerol conversion and product selectivities were also studied in this work. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propanediol; Alkali fusion; Cu loading; Fly ash; Glycerol hydrogenolysis

Carbonylation of glycerol with urea to glycerol carbonate over supported Zn catalysts - Kondawar, S. E.; Mane, R. B.; Vasishta, A.; More, S. B.; Dhengale, S. D.; Rode, C. V. (Applied Petrochemical Research, 2017)
Glycerol carbonylation with urea is a very feasible option to produce glycerol carbonate with a net result of CO2 fixation through urea synthesis. The prerequisite of an efficient catalyst for this reaction is to possess both acid and basic sites together. Several acidic supports were screened for ZnO catalyst in this work and Zn/MCM-41 was found to exhibit the best activity and almost complete selectivity to glycerol carbonate (GC). Although, non-catalytic glycerol carbonylation resulted in GC formation but glycerol conversion achieved was twice with Zn/MCM-41 as a catalyst. Further to that increase in Zn loading from 2 to 5% resulted in increase in glycerol conversion from 63 to 82%. The prepared catalysts were characterized by XRD, NH3 and CO2-TPD and effects of reaction parameters such as catalyst loading, glycerol to urea mole ratio and temperature on glycerol conversion and GC selectivity in batch mode of operation were also studied. Time on stream activity of 5% Zn/MCM-41 catalyst for continuous carbonylation of glycerol was also studied for ~100 h with an average conversion of ~55% and complete selectivity to GC. This indicated five times lower productivity of GC per h due to lower residence time than that in a batch operation as compared to that of a continuous operation. Activation energy estimated from the Arrhenius plot was found to be 39.82 kJ mol−1 suggesting that the reaction is kinetically controlled. A reaction pathway mediated by acid and basic sites of the Zn/MCM-41 catalyst is also proposed.
Keywords: Acid–base ratio; Continuous process; Glycerol carbonate; Glycerol-urea carbonylation; reaction pathway; Supported Zn; Zn loading

Cascade dehydrative amination of glycerol to oxazoline - Pandya, R.; Mane, R.; Rode, C. V. (Catalysis Science & Technology, 2018)
Transformation of biomass into valuable nitrogen-containing compounds is highly desired, yet less explored. Here, we report a simple and efficient method for the direct conversion of bioglycerol to oxazoline involving glycerol dehydration to acetol followed by its amination using an aqueous solution of ammonia. For the two-step strategy a non-noble metal Cu-Zr catalyst was developed, giving a glycerol to acetol conversion of 78% followed by amination separately with 95% selectivity to oxazoline. Moreover, we have demonstrated a single-pot oxazoline synthesis using Ru/C as the most stable catalyst to achieve 95% selectivity to oxazoline without any leaching. XPS studies revealed the co-existence of multivalent Ru species in different percentages depending on the nature and structure of the support. These multivalent species (RuO2 and RuO3) have a synergistic effect on the activation of the carbonyl group, whereas Ru-0 is an active site for ammonia dissociation. NH3-TPD and Py-IR spectroscopy results also suggest that the presence of relatively moderate acid sites and a higher BrOnsted/Lewis acid ratio in the catalyst promote the selective production of oxazoline. The reaction pathway involves first glycerol dehydration to acetol. In the subsequent step, NH3 is dissociatively adsorbed on the catalyst surface and the imine thus formed is condensed with a second molecule of acetol to obtain oxazoline. The studied catalyst could be recycled successfully without any significant loss of catalytic activity.

Cascade dehydrative amination of glycerol to oxazoline (vol 8, pg 2954, 2018) - Pandya, R.; Mane, R.; Rode, C. V. (Catalysis Science & Technology, 2020)
Correction for `Cascade dehydrative amination of glycerol to oxazoline' by R. Pandyaet al.,Catal. Sci. Technol., 2018,8, 2954-2965, DOI: ;10.1039/C8CY00185E.